Improving Students™ Vocabulary Mastery by Using Realia - Sukrina, Vina (Universitas Negeri Medan, 2013)
ABSTRACTThis study was attempted to discover the improvement studentsŸ vocabulary mastery by using realia for elementary studentsŸ Grade IV. The objective of this study was to find out whether realia can significantly improve studentsŸ vocabulary or not. In this study, the writer was conducted by Applying Classroom Research. The subject of this study was one class of the grade IV studentsŸ of SD Negeri 060811 Medan which consisted of 36 studentsŸ. The quantitative data were taken from vocabulary test as the instrument to find out the studentsŸ score. The qualitative data taken from diary notes and observation sheet describe the improvement of the studentsŸ vocabulary mastery of the studentsŸ vocabulary mastery was mostly improved in every test. The range of improvement of the first test and the last test was 83,33%. The observation sheet and the diary notes showed that the studentsŸ were interested in the teaching learning process. These finding show that there was an improvement on the studentsŸ vocabulary through realia that was supported by the result, the mean score of the second test (64,44) was better than mean score of first test (39,17), and the mean score of the third test (78,05) was better than the mean score of the second test. This implies that realia can be an alternative strategy in improving studentsŸ vocabulary mastery. It is suggested that realia to be used in teaching vocabulary especially to young learners.Keywords: Vocabulary Mastery, Realia Media, Procedure of Teaching Vocabulary.